Integrative Learning Strategies for Enhancing Critical Thinking in Islamic Religious Education - Dalimunthe, Muhammad Aidil; Siregar , Panyahatan (IDRIS Darulfunun Institute, 2024)
This research employs a qualitative approach to explore integrative learning strategies aimed at enhancing critical thinking skills in Islamic Religious Education at the secondary school level in Padang, Indonesia. The study involved four teachers and 120 students from various classes to provide a comprehensive perspective. Given the increasing importance of critical thinking in education, especially in subjects that shape students' moral and ethical foundations, this research emphasizes the crucial role of developing these skills within Islamic Religious Education. Data were collected through direct classroom observations, in-depth interviews with teachers and students to capture their experiences and insights on the strategies used, and a detailed analysis of relevant teaching materials. The findings reveal that group discussions create a dynamic environment where students can exchange ideas, broaden perspectives, and develop critical arguments. Case study analyses enable students to connect religious concepts to real-life situations, reinforcing the practical significance of religious teachings. Problem-solving activities promote logical, systematic, and reflective thinking skills, especially when addressing complex moral and ethical dilemmas. The study also highlights that these strategies not only enhance students' critical thinking but also increase their active engagement in learning, deepen their understanding of religious teachings, and foster a reflective approach toward moral values. This research offers an in-depth understanding of the effectiveness of integrative learning strategies in Islamic Religious Education and underscores their relevance in preparing students to meet the demands of modern education, which prioritizes critical thinking skills.